Corporalidade brasileira na fabricação da identidade nacional - Castro, Ana Lúcia de [UNESP]; Pires, Renata (My University, 2014)
This paper discusses how, through the creation of Embratur (Brazilian Tourism Company) in 1966, an idealized Brazilian female body was constructed and used to help manufacture a national identity, reinforcing the stereotype of the sexualized Brazilian woman. As it was often associated with sex tourism, this stereotype received much criticism and led to a negative image of Brazil abroad. However, in the 1990s the official tourism lobby softened the “sexy tone” of its discourse, and in 1999 Embratur received an award from the World Tourism Organization for its campaign to help fight the exploitation of children and youth by sexual tourism. In order to better understand how this change in the idealized Brazilian female body unfolded, it is important to deconstruct beauty standards – focusing on those that apply to Brazilian women as seen from abroad – and their relationship to modern consumer culture. Assuming that the cultural analysis of the female body emerges as an important issue in the field of Social Science, the focus on body image can be viewed as a key element in discussions about the construction of national identity.

O presente ensaio pretende discutir a maneira como um ideal de corpo feminino brasileiro foi construído historicamente e instrumentalizado na fabricação de uma identidade nacional a partir da criação da Embratur, em 1966, reforçando o estereótipo de mulher brasileira sensual. Esta instrumentalização do corpo da mulher brasileira recebeu muitas críticas e levou à construção de uma imagem negativa do Brasil no exterior, associada ao turismo sexual; contudo, a partir dos anos 90, os discursos oficiais de divulgação turística amenizaram o tom “sensual”, o que acabou levando a Embratur a receber, em 1999, o prêmio da Organização Mundial do Turismo pela sua Campanha de Combate à Exploração do Turismo Sexual Infantojuvenil. Para melhor percorrermos a trajetória desta mudança de imagem, faz-se necessário problematizarmos os padrões de beleza corporal – focando nas especificidades do padrão de beleza da mulher brasileira, sempre tão propagado em outros países – e sua relação com a cultura de consumo contemporânea. Partindo do pressuposto de que a análise cultural do corpo vem se revelando um tema importante para as ciências sociais, o foco na corporalidade pode ser tomado como um elemento-chave nas discussões acerca dos processos de construção de identidades nacionais.
The body of Brazilian women in the construction of national identity
Keywords: National identity; Body and culture; Consumption; Identidade nacional; Corpo e cultura; Consumo cultural